2012
DOI: 10.1086/668021
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Mycobacterium mucogenicum Bloodstream Infections among Patients with Sickle Cell Disease in an Outpatient Setting

Abstract: The source of the M. mucogenicum bacteremia outbreak was identified by genotyping analysis as the clinic tap water supply. The preparation of intravenous medications near the sink was likely an important factor in transmission, along with the presence of a faucet aerator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Moreover, the result of the environment/water culture and type matching of isolates from the blood cultures with isolates from the environmental/water cultures indicated that the origin of these organisms was the tap water supply. As with previous instances, 8,9,19 we considered the portal of entry for both of these organisms into the bloodstream in this outbreak was likely to be the submersion of CVC during bathing, showering, or toileting. Enhancing the CVC dressing prior to bathing or showering is crucial.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the result of the environment/water culture and type matching of isolates from the blood cultures with isolates from the environmental/water cultures indicated that the origin of these organisms was the tap water supply. As with previous instances, 8,9,19 we considered the portal of entry for both of these organisms into the bloodstream in this outbreak was likely to be the submersion of CVC during bathing, showering, or toileting. Enhancing the CVC dressing prior to bathing or showering is crucial.…”
Section: Discussionmentioning
confidence: 90%
“…5,6 Although the incidence of CLABSI due to RGM, especially M. mucogenicum, in hematopoietic stem cell transplant recipients or patients on intense immunosuppressive agents, appears to be low, 6 outbreaks of bloodstream infections among such patients have been reported between 2004 and 2012 (although the outbreak reported in 2004 actually occurred in 1998; Table 2). 8,9,11,[18][19][20] In this outbreak, 4 of 5 patients received dressing changes at the catheter site owing to submersion of the catheter during showering. Moreover, the result of the environment/water culture and type matching of isolates from the blood cultures with isolates from the environmental/water cultures indicated that the origin of these organisms was the tap water supply.…”
Section: Discussionmentioning
confidence: 99%
“…Higher prevalence rates were found in patients in this region with sickle cell disease [ 6 ]. Finally, an outbreak study of confirmed Mycobacterium mucogenicum bloodstream infections indicated that the four infected sickle cell disease patients had iron overload [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a modest number of mycobacterial infections have been reported in sickle cell disease. Those patients however were otherwise immunocompentent which raises the query of an alternative susceptibility in this patient population [ 5 8 ]. While sickle cell disease patients are known to be vulnerable to infections, there lacks explanation for susceptibility to mycobacterial organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Because the organisms occur frequently in hospital tap water [6770], many true outbreaks and several pseudo-outbreaks with NTM have been reported. Hospital-associated outbreaks and sporadic cases have included central line infections, sternal wound infections, cosmetic surgery-associated soft tissue infections, and bloodstream infections related to dialysis [7180]. Most reported outbreaks involved exposure of invasive devices or nonintact skin to tap water.…”
Section: Mycobacteriamentioning
confidence: 99%